Compressive study on recycled concrete: experiment and numerical homogenization modelling - Fellah Djamel; Barboura Salma; Tilmatine Thileli; Benyahi Karim; Li Jia; Bouafia Youcef (Fracture and Structural Integrity)
This paper describes a study of recycled concrete under compressive loads. The study was conducted in two main parts. In the first part, experimental tests were carried out on concrete samples with varying levels of substitution (25%, 50%, and 75%) with recycled aggregate in order to measure the mechanical properties of the recycled concrete. In the second part of the study, a nonlinear homogenization model was developed on the basis of a classical secant approach to predict the behavior of recycled concrete. In this model, we assume that the behavior of the mortar phase, the concrete, and the recycled aggregates follow Mazars damage law. Comparison with the experimental data shows that the proposed homogenization model is accurate and efficient in predicting the correct nonlinear behavior of the recycled concrete. By better understanding the properties and behavior of recycled concrete, it will be possible to develop more effective methods for incorporating recycled materials into concrete structures